2011
DOI: 10.1590/s1413-70542011000600004
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of aqueous extracts of Clibadium sylvestre (Aubl.) Baill. and Derris amazonica Killip on the aphid Myzus persicae (Sulzer, 1776) (Hemiptera: Aphididae)

Abstract: Studies with botanical insecticides have become more popular as an alternative to Integrated Pest Management. The purpose of this study was to evaluate the effect of leaf and fruit aqueous extracts, from the species Clibadium sylvestre, and leaves and root of Derris amazonica species at concentrations of 0, 1, 2, 4 and 8%, in the control of the aphid Myzus persicae (Hemiptera: Aphididae). Four experiments were conducted; two tests with choice preference and two tests with no choice preference, giving nine trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Flavonoids such as quercetin participate in important processes, including development and plant defense, inhibition of the regulation of digestive enzymes, strengthening of plant cell walls, and decrease in the palatability to herbivores (Schoonhoven et al, 2005;Chen, 2008;Filgueiras et al, 2011). Vandock et al (2012) reported that flavonoids affect enzymes, preventing enzymatic reactions that are vital to the development, and are considered anti-nutritional and highly toxic to insects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids such as quercetin participate in important processes, including development and plant defense, inhibition of the regulation of digestive enzymes, strengthening of plant cell walls, and decrease in the palatability to herbivores (Schoonhoven et al, 2005;Chen, 2008;Filgueiras et al, 2011). Vandock et al (2012) reported that flavonoids affect enzymes, preventing enzymatic reactions that are vital to the development, and are considered anti-nutritional and highly toxic to insects.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, they concluded that their toxicity is derived from reactive oxygen species such as semiquinone radicals and quinones, which are formed by oxidation of tannins in insects' high intestinal pH. Flavonoid quercetin, also identified in ABF, is known to decrease the palatability of plant tissues to herbivores and to inhibit enzymatic reactions that are vital for insect development (Filgueiras et al, 2011;Vandock et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…These compounds are powerful stimulants of the central nervous system, and their convulsant activity has been demonstrated in mammals and fish to involve the GABAergic system (COSTA et al, 2006;hAMOy et al, 2018). Because mosquitoes of the genus Aedes also have GABA as a neurotransmitter, they are vulnerable to the neurotoxic activities of cunaniol and Phytochemical analysis of leaves and fruits of C. sylvestre revealed tannins to be the most common secondary metabolites in this plant (FILGueIRAS et al, 2011). Tannins have several known biological functions, such as larvicidal activity (NeRy et al, 2009), which was demonstrated by Silva et al (2004) using an extract from Magonia pubescens.…”
Section: Discussionmentioning
confidence: 98%
“…on the second- and fourth-instar larvae of Spodoptera littoralis , leading to mortality; W. solanacea and Witheringia coccoloboides (Dammer) were shown to contain cytotoxic compounds, whereas Clibadium sp. contains tannins, glycosides, sesquiterpenes, carotenoids, terpenoids, essential oils, and alkaloids (Filgueiras et al 2011), which may explain the decreased leaf consumption by larvae. The latter two species also contain inorganic salts such as oxalic acid, which results in the formation of oxalate (Sefa-Dedeh and Agyir-Sackey 2004, Chávez and Enriquez 2013) in Xanthosoma poeppigii and calcium oxalate (Finley 1999) in D. costata .…”
Section: Discussionmentioning
confidence: 99%